Zero-Valent Iron (ZVI) for groundwater remediation - Sethy N.K.; Arif Z.; Sista K.S.; Kumar P.; Mishra P.K.; Saha R. (My University, 2025)
Groundwater is one of the prominent sources of usable water for human beings across the globe. The quality of groundwater is being compromised due to the advent of harmful pollutants from natural and anthropogenic activities sourced from rapid urbanization and industrialization. Many treatment techniques like oxidation, precipitation, coagulation, disinfection, adsorption, ion exchange, etc., using various chemicals like chlorine, ozone, aluminium sulphate, ferrous chloride, sodium aluminate, activated carbon, activated alumina, zeolites, iron, natural clay, etc., are in practice for groundwater remediation. One such prominent material, which imparts one or a combination of adsorption, reduction, oxidation, precipitation, and co-precipitation principles for multi-contaminant removal from groundwater is zero-valent iron (ZVI). ZVI is widely used for removal of metalloids (As), heavy metals (Cr, Ni, Pb, Zn), nitrates, phosphates, chloro-organic compounds, nitro amino compounds, dyes, phenol compounds, etc. This unique material, ZVI, possesses several advantages, including high reactivity, wide availability, multi-component removal, no sludge, flexibility, low cost and technology ease, and few limitations of thick oxide formation, foreign particle hurdle, and narrow pH operation. This chapter showcases the usage of ZVI in groundwater remediation. More focus is laid to elucidate the synthesis and mechanism of ZVI, along with various research works reported. Recent advancements in ZVI research are inclined towards the synthesis of novel and modified ZVI and the future of ZVI technology is in its usage along with proper support of physical, chemical, or a combination of technologies, as well as its integration with other water treatment technologies to achieve superior contaminant removal from groundwater. © 2021 John Wiley & Sons Ltd. All rights reserved.